EFFECTS OF WATER, KOH, HCl AND IONIC STRENGTH ON SWELLING CAPACITY OF CARBOXYMETHYL CELLULOSE (CMC) BASED GRAFT COPOLYMER HYDROGEL - Yahaya, S.; Zauro, S. A.; Ibrahim, U.; Tolani, A. M.; Shinkafi, I. Y.; Albashir, Y. (FUDMA JOURNAL OF SCIENCES, 2023)
Hydrogels are three-dimensional crosslinked polymers with several uses in the administration and loading of drugs as well as the capacity to hold enormous amounts of water or biological fluids. Using carboxymethyl cellulose, N,N-dimethyl acrylamide (DMA), 2-acrylamido-2-methyl-1-propane sulphonic acid (AMPS), N,N-bisacrylamide (MBA) as a crosslinker, and potassium persulate (KPS) as an initiator, the CMC-g-poly(DMA-co-AMPS) was created. FTIR spectroscopy was used to characterize the CMC-g-poly(DMA-co-AMPS). In distilled water, KOH, and HCl, the CMC-g-poly(DMA-co-AMPS)’s swelling capability was assessed. CMC-g-poly(DMA-co-AMPS has the largest swelling ratio in KOH, followed by HCl, while pure water has the lowest swelling ratio. Various salt solutions (FeCl3.6H2O, CuCl2, and NaCl) were used at predetermined times in distilled water to test the effect of ionic strength on CMC-g-poly(DMA-co-AMPS). The swelling of CMC-g-poly(DMA-co-AMPS) increased with the increase in salt solution concentration, and the ionic strength of a solution is the measure of the concentration of ions in salt solutions. In salt solutions (CuCl2, NaCl, and FeCl3.6H2O), the maximal swelling ratio of CMC-g-poly(DMA-co-AMPS) is 10.5g, 10.0g, and 9.5g, respectively.